Dimensionamento de um sistema de painéis solares para a produção de hidrogênio a partir de eletrolisador no LH2M/DEMa/UFSCar - Romano, Lucas Fernando (Universidade Federal de São Carlos, 2024)
The Center for Advanced Materials and Energy Research (CPqMAE) is a Multidisciplinary Unit of the Center for Exact Sciences and Technology (CCET) at UFSCar. Among the laboratories within this center is the Hydrogen in Metals Laboratory (LH2M), which is responsible for the development of technologies for hydrogen production and storage. With the ongoing global technological development, resulting in increased consumption of electricity and non-renewable sources such as oil, coal, and natural gas, there is a quest for renewable energy solutions such as solar power. In this study, the sizing of an off-grid photovoltaic system connected to an electrolyzer was conducted, aiming at hydrogen production, and its economic viability was also assessed through positive NPV, for the implementation of the project at LH2M of UFSCar. For the sizing, 54 photovoltaic modules of 660 W Vertex model and a 12 kW PEM electrolyzer LBEX-P20K were used.
Sizing of a solar panel system for hydrogen production from an electrolizer at LH2M/DEMa/UFSCar
Keywords: Hidrogênio; Painel Solar; Eletrolizador; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA